Fungus-associated asthma: overcoming challenges in diagnosis and treatment. (May 2014) - Ogawa, Haruhiko; Fujimura, Masaki; Ohkura, Noriyuki; Satoh, Kazuo; Makimura, Koichi
<x xml:space="preserve">Abstract</x> With regard to fungal colonization and fungal sensitization, the goals of fungus-associated asthma management are as follows: 1) to survey fungi colonizing the airways of patients repeatedly; 2) to evaluate the tendency of the colonizing fungi to sensitize patients and the influence on clinical manifestations of asthma; 3) to follow disease development to allergic bronchopulmonary mycosis or sinobronchial allergic mycosis; and 4) to determine whether fungal eradication from the airway of patients is beneficial from the viewpoints of future risk factors. Recent developments in molecular biological analyses have facilitated the identification of basidiomycetous fungi that were not previously thought to be of concern in fungal allergy. The total control of fungus-associated asthma will be accomplished by environmental management established from the viewpoint of both the ecology and life cycle of the responsible fungi.